Impact of Single versus Double Clamp Technique on Blood Lactate Levels and Postoperative Complications in Coronary Artery Bypass Surgery - Özmen,Rifat (2022)
Abstract Introduction: Cardiopulmonary bypass (CPB) is associated with hyperlactatemia, which leads to adverse clinical outcomes. No study has examined the effect of different clamping techniques on postoperative hyperlactatemia (PHL). Thus, we aimed to evaluate the impact of two different techniques on PHL and the clinical outcomes in patients undergoing isolated coronary artery bypass surgery. Methods: This retrospective study included 100 patients who underwent isolated CPB either with single clamp technique (SCT, n=47) or double clamp technique (DCT, n=53). Demographic and preoperative laboratory data, as well as operative features and arterial blood lactate levels at the onset and at the end of CPB, were collected from patient charts. Results: Blood lactate levels collected at the end of CPB did not differ significantly between groups whereas intraoperative lactate increased significantly in both groups (P<0.005). PHL developed in 16 patients (32%). There was no meaningful difference in SCT and DCT in this regard. Left internal mammary artery was used more frequently in the DCT group than in the SCT group. While the cross-clamp time was significantly longer in the SCT group, there was no difference regarding CPB time. Among postoperative complications, only the incidence of stroke was significantly higher in the DCT group than in the SCT group (10.6% vs. 0%, P=0.020). CPB time, cross-clamp time and numbers of proximal saphenous graft and distal anastomosis showed a significant positive correlation with the postoperative lactate level. In the regression analysis, CPB time emerged as the only independent predictor of PHL (OR 1.04, CI 95% 1.01-1.07, P=0.011). Conclusion: There was no difference in postoperative blood lactate levels between SCT and DCT groups.